Perbedaan Pengetahuan dan Sikap terhadap Manfaat Vitamin D pada Mahasiswa Kesehatan dan Non-Kesehatan - Rifaatul Laila Mahmudah; Amelia Lorensia; Asti Indah Purwati (STIKes Surya Global Yogyakarta, 2021)
ABSTRACTBackground of Study: Vitamin D deficiency can be a serious problem that can be prevented early on. An unfavorable young lifestyle can affect vitamin D in the body due to the level of knowledge and attitudes towards the benefits of vitamin D, including students. This study aimed to determine the differences in knowledge and attitudes towards sun exposure in health and non-health studentsMethods : The design of this study was cross sectional., in September–December 2017. The variables of this study were health and non-health students, and knowledge and attitudes related to vitamin D. The research sample was active students at a university in Surabaya. Methods of collecting data using a questionnaire and data analysis using chi-square test.Results : This study involved 100 health student respondents and 100 non-health students. The results of the chi square test show that the level of knowledge of the P value (0.000) 0.05 means that there was a significant difference in knowledge of sun exposure in the two groups. While the results of the attitude level P value (0.447) 0.05 meaned that there was no significant difference in attitudes towards sun exposure in the two groups.Conclusion : Students' knowledge of health was higher than that of non-health, although there was no difference in attitude level between the two.Keywords : knowledge, attitude, vitamin D, students